Characterization of opioid receptors in golden hamster brain - WU Shi-wei; JIN Wen-qiao; CHI Zhi-qiang (Acta Pharmacologica Sinica, 2016)
The nature of opioid receptors in golden hamster brain has been studied in this paper. The results of experiments indiated that specific binding of the three [3H]ligands in concentration-dependent and saturable. Scatchard analysis showed that the Kd and Bmax were 1.3 nmol/L an 17.8 pmol/g protein, respectively for mu binding, 0.99 nmol/L and 11.6 pmol/g protein, respectively for delta binding and 0.30 nmol/L and 22.8 pmol/g protein, respectively for kappa binding. Competition binding studies indicated that cold mu ligand, ohmefentanyl easily displaced the binding of [3H]DAGO [K1=(2.6+/-0.3)*10(-11) mol/L]. Relatively selective delta ligand, DADLE, readily inhibited the binding of [3H]DADLE [K1=(1.0+/-0.5)*10(-9) mol/L]. However, selective kappa ligand, U-50488H competed effectively the binding of [3H]etorphine to kappa receptors [K1=(3.2+/-0.1)*10(-9) mol/L]. Based on our experiments, we estimate that the golden hamster brain contains 44% kappa, 34% mu and 22% delta receptors. These results suggest that the high binding to kappa receptors exists predominantly in the golden hamster brain. It markedly differs from the brains of rat or guinea pig. The brain tissue of golden hamster may be a better material for studying of kappa receptors.